Genetics, evolution, and biological control - Ehler, Lester E.; Sforza, R. (Rene); Mateille, T. (Thierry) (CABI Pub., 2004)
This book is the result of the 12 keynote addresses, delivered at the third IOBC International Symposium held in Montpellier, France in October 2002, focusing on recent developments in genetics and evolutionary biology, and their relevance to biological control. Chapters are organized around the following themes: genetic structure of pest and natural enemy populations; molecular diagnostic tools in biological control; tracing the origin of pests and natural enemies; predictive evolutionary change in pests and natural enemies; compatibility of transgenic crops and natural enemies; and genetic manipulation of natural enemies. This book will interest readers in entomology and pest management, genetics, ecology and evolution.